Description of the larva of Bromeliagrion rehni (Odonata: Coenagrionidae) with bionomic notes concerning its phytotelmic habitat in central Amazonas, Brazil - Torreias, Sharlene Roberta da Silva (2008)
The last-stage larva of Bromeliagrion rehni Garrison in De Marmels & Garrison, 2005 is described and illustrated and bionomics and habitat information on this species are provided. The study was conducted in the Reserva Florestal Adolpho Ducke, located near Manaus, state of Amazonas, Brazil.Twelve samplings were done between April, 2003 and April, 2005: six in the rainy season and six in the dry season. In each sampling month, 12 bromeliads (Guzmania brasiliensis Ule, 1907, Bromeliaceae) were collected, six of which were terrestrial and six epiphytic, yielding144 samples. A total of 75 specimens of B. rehni were collected. The relationship between larval B. rehni abundance and the measured environmental parameters (volume (ml), pH, season and stratum) was significant (ANCOVA, F = 5.296, d.f. = 130, p < 0.001). Larvae were most abundant in the rainy season (p < 0.01) and water volume was positively related to the abundance of B. rehni. Larvae of B. rehni can be distinguished from those of B. fernandezianum (the only species in the genus with described larvae) by the number of setae in the prementum and by the color of the apical region of the femur. The association of this species with phytotelmata of G. brasiliensis is reported here for the first time.